2012
DOI: 10.1021/am302069p
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Novel Cholic Acid Modified OPE-Based Fluorescent Film and Its Sensing Performances to Inorganic Acids in Acetone

Abstract: A self-assembled monolayer (SAM)-based fluorescent film was designed and prepared by chemical immobilization of a novel oligo(p-phenylene- ethynylene) (OPE) with cholic acid moieties at the ends of its side chains (Film 1). As a control, a similar film, Film 2, of which OPE brings no side chains, was also prepared. The structures of the films were characterized by contact angle, XPS, ATR-IR and fluorescence measurements. Fluorescence studies revealed that the emission of Film 1 is sensitive to the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…211 Generally, the sensing of the SAM film with the one-molecule-thick layer occurs in a short response time. 213 The introduction of cholic acid (CholA) into the side-chains of OPE prevented the aggregation of the OPE backbones and improved the solubility in organic media, promoting the covalent attachment of CholA-OPE to the silane layers on the surface of the substrate. In this section, the current progress on the luminescent film based on the SAM technique is presented.…”
Section: Luminescent Films Via the Selfassembled Monolayer (Sam) Methodsmentioning
confidence: 99%
“…211 Generally, the sensing of the SAM film with the one-molecule-thick layer occurs in a short response time. 213 The introduction of cholic acid (CholA) into the side-chains of OPE prevented the aggregation of the OPE backbones and improved the solubility in organic media, promoting the covalent attachment of CholA-OPE to the silane layers on the surface of the substrate. In this section, the current progress on the luminescent film based on the SAM technique is presented.…”
Section: Luminescent Films Via the Selfassembled Monolayer (Sam) Methodsmentioning
confidence: 99%
“…A large excess of 1,8-dibromooctane was used to prevent two-fold reaction on one alkyl chain and potassium carbonate was found to give better yields than sodium hydroxide 16 or sodium hydride (in ethanol). Both monomers (5 and 7) needed for the Sonogashira polymerization reaction were synthesized via similar pathways (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…1, right part). [43][44][45] Unlike the construction of SA-2D films based on a low-molecular-mass fluorophore, the creation of novel SA-2D films based on a conjugated polymer or oligomer is hard to achieve via simply varying the linker structures, which is one of the most commonly adopted strategies in the creation of films with novel structures and properties. It is believed that most of the sensing sites are exposed in the monolayer film and are easily reached by the analyte.…”
Section: Conventional Fluorescent Sensing Filmsmentioning
confidence: 99%
“…(Fig. 44 It was demonstrated that the two CholA moieties that were attached to the side chains of the fluorophore not only affected the fluorescence behavior of the film, but also favored the formation of hydrophilic pockets above the BPEB adlayer when the film was exposed to acetone. Fluorescence and molecular dynamics modeling studies revealed that the long, flexible alkyl chains played a crucial role in the smart sensing performance of the oligomer-based film.…”
Section: Conventional Fluorescent Sensing Filmsmentioning
confidence: 99%